2015
DOI: 10.1080/02678373.2014.1003995
|View full text |Cite
|
Sign up to set email alerts
|

Health and well-being of older workers: comparing their associations with effort–reward imbalance and Pressure, Disorganisation and Regulatory Failure

Abstract: Work organisation has well-established associations with health. This study compares the associations of Pressure, Disorganisation and Regulatory Failure (PDR) and effort-reward imbalance (ERI) with health and well-being among older workers. Participants were 714 Australian workers aged 45-65 (56.3% female), with a mean age of 54.6 years (SD = 5.0) and a mean of 34.7 working hours per week (SD = 13.9). Hierarchical regression analyses tested the strengths of the associations of both ERI and PDR with work-life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 45 publications
1
36
0
1
Order By: Relevance
“…Gender was measured with a dichotomous variable coded “0” for female and “1” for male. Financial pressure was assessed with the mean score of three items (e.g., “I have money left over at the end of the month” and “I make just enough money to make ends meet”) from the Pressure, Disorganization and Regulatory Failure scale (alpha = 0.65) (Bohle et al, 2015). A median split on the financial pressure composite was used as a grouping variable to reflect higher and lower financial pressure groups.…”
Section: Methodsmentioning
confidence: 99%
“…Gender was measured with a dichotomous variable coded “0” for female and “1” for male. Financial pressure was assessed with the mean score of three items (e.g., “I have money left over at the end of the month” and “I make just enough money to make ends meet”) from the Pressure, Disorganization and Regulatory Failure scale (alpha = 0.65) (Bohle et al, 2015). A median split on the financial pressure composite was used as a grouping variable to reflect higher and lower financial pressure groups.…”
Section: Methodsmentioning
confidence: 99%
“…The continued controversy over whether labour markets are transitioning away from the SER to a model of employment that is less secure speaks to the need to explore in more detail how to measure employment precarity and what exactly the form of the employment relationship is measuring. There are several ongoing efforts to develop measures of employment precarity that go beyond simply measuring the form of the employment relationship (Bohle et al, 2015; Gallie et al, 2017; Goldring and Landolt, 2009; Lewchuk et al, 2011; Puig-Barrachina et al, 2014; Vives et al, 2010; Vosko, 2006). In an interesting recent article, Gallie et al (2017) have suggested measuring two related components: job tenure insecurity and job status insecurity.…”
Section: The Form Of the Employment Relationship As An Indicator Of Ementioning
confidence: 99%
“…В целом изучение особенностей профессионального развития в поздней зрелости показывает их обусловленность психофизиологическими характеристиками (L. Claudon [47], P. Bohle [48], M. Sanders [49]), влиянием окружающей среды (А. И. Мелёхин [39], П. Д. Косинский, Н. С. Бондарев, Г. С. Бондарева [40]), внутренней мотивацией к продолжению профессиональной деятельности (А. Г. Эфендиев, К. В. Решетникова [41], Д. Г. Гадеева [42]) и востребованностью в профессиональном сообществе (Е. В. Игнатьева, Ю. В. Рябкова [43], А. М. Дубровин [44]).…”
Section: обсуждение результатовunclassified